Chicago's white city of 1893 - Burg, David F. (Ebsco e-books., 1976)
In 1893, the year that marked the four hundredth anniversary of the landing of Columbus in the New World, Chicago was host to an exposition to mark the occasion. Although the World's Columbian Exposition was the fifteenth world's fair, it was of vastly greater scope than any of its predecessors. Chicago created a veritable new city. It was not only larger than any previous exposition but also more elaborately designed, more precisely laid out, more fully realized, and more prophetic. It was the first exposition truly to solicit the participation of the entire world. In this study of the White C.